The effect of cement aging on the stability of a cement-in-cement revision construct - Schonhoff, Mareike; Bormann, Therese; Knappe, Kevin; Reiner, Tobias; Stange, Linda; Jäger, Sebastian (Applied Sciences, 2021)
A revision surgery can be a complicated procedure. The prevention of the removal of a well-integrated cement mantle can minimize intraoperative complications. With the cement-in-cement technique, the implant will be fixated with a layer of bone cement onto the remaining cement mantle. In our experimental in vitro study, we investigated the effect of cement aging of a cement-in-cement revision construct and regular cement mantle on the bending strength. Two different types of bone cement were tested at four different stages of aging. The Palacos cement showed no significant difference in bending strength at any aging point, regardless of whether it was used primarily or as a cement-in-cement revision. In contrast, the SmartSet MV cement showed a significant difference between the primary and cement-in-cement applications depending on cement aging time. The comparison of the two cement-in-cement structures investigated showed significant differences between the manufacturers depending on the cement aging.
Gesehen am 18.05.2021